Penerapan Balanced Scorecard Pada Pengukuran Kinerja PT. Blue Bird Tbk. - Djo, Noviana Hermanus; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2019)
The variables of this study are the four perspectives of the Balanced Scorecard, which are financial perspectives that are measured by ROI, corporate planning, supervision and control of the company, customer perspectives that are measured by reliability, responsiveness, assurance, empathy and invisible, internal business process perspectives that measure innovation , operations and post-sales, learning and growth perspectives are measured by job satisfaction and employee motivation. Results from the four perspectives indicate that the performance of PT. Blue Bird Tbk. In terms of: (1) financial perspective is not good with ROI which decreases every year but management is good, (2) customer perspective is good with customers satisfied with reliability, responsiveness, assurance, empathy, and invisible, (3) internal business process learning and growth perspective is good with the satisfaction and motivation of employees. Keywords : Balanced scorecard, performance measurement, financial perspective, customer perspective